Have Video Games Evolved Enough to Teach Human Origins?: A Review of Ancestors: The Humankind Odyssey. Issue 1 (February 2022) - Snyder, William D.
Overview: Video games are unparalleled as an interactive medium and can serve as potential educational tools through intelligent game design and the players' immersion in the game world (e.g., Mayo 2009; Rassalle 2021; Rubio-Campillo 2020; Winter 2021). At the same time, video games, like any media, might also misinform (e.g., Aron 2020; Dennis 2019; Emery and Reinhard 2016). In this review, I present my impressions of the game Ancestors: A Humankind Odyssey (Panache Digital Games 2019), specifically regarding its portrayal of paleoanthropological themes. In preparing this review, I played the game in its entirety and subsequently interviewed the developers in order to clarify their intentions when designing the game (Patrice Désilets and Marc-André De Blois, personal communication 2021). Using the medium of video games, is it possible to make a "perfectly" accurate simulation of human evolution? Perhaps, but that may not matter anyway. In my view, video games, as exemplified by Ancestors, have great potential for exploring the basic components of human evolution and to reach and inspire a wider public that might otherwise learn very little about the subject matter.